2020
DOI: 10.1186/s12889-019-8103-4
|View full text |Cite
|
Sign up to set email alerts
|

Sick leave absence and the relationship between intra-generational social mobility and mortality: health selection in Sweden

Abstract: Background: Poor health could influence how individuals are sorted into occupational classes. Health selection has therefore been considered a potential modifier to the mortality class gradient through differences in social mobility. Direct health selection in particular may operate in the short-term as poor health may lead to reduced work hours or achievement, downward social mobility, unemployment or restricted upward mobility, and death. In this study, the relationship between social mobility and mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 43 publications
1
10
0
Order By: Relevance
“…Eight prospective or retrospective cohort studies showed a higher rate of suicide during follow-up among people with a sickness absence spell during the study inception period, compared to those without sickness absence (32)(33)(34)(35)(36)(37)(38)(39). Multiple of these studies observed that people with longer sickness absence spells, and those with multiple spells, are at increased risk of suicide than those with short or no absences (32,33,36,38), and that those whose absence is due to mental health conditions are at increased risk of suicide (34)(35)(36)(37)(38).…”
Section: Intentional Self-harmmentioning
confidence: 99%
See 1 more Smart Citation
“…Eight prospective or retrospective cohort studies showed a higher rate of suicide during follow-up among people with a sickness absence spell during the study inception period, compared to those without sickness absence (32)(33)(34)(35)(36)(37)(38)(39). Multiple of these studies observed that people with longer sickness absence spells, and those with multiple spells, are at increased risk of suicide than those with short or no absences (32,33,36,38), and that those whose absence is due to mental health conditions are at increased risk of suicide (34)(35)(36)(37)(38).…”
Section: Intentional Self-harmmentioning
confidence: 99%
“…Eight prospective or retrospective cohort studies showed a higher rate of suicide during follow-up among people with a sickness absence spell during the study inception period, compared to those without sickness absence (32)(33)(34)(35)(36)(37)(38)(39). Multiple of these studies observed that people with longer sickness absence spells, and those with multiple spells, are at increased risk of suicide than those with short or no absences (32,33,36,38), and that those whose absence is due to mental health conditions are at increased risk of suicide (34)(35)(36)(37)(38). Two of these cohort studies observed similar associations between mental health related sickness absence, and sick leave duration, and intentional self-harm (38,39), while other studies also observed that there was increased rate of suicide or intentional self-harm in people with sickness absence due to musculoskeletal disorders (38) (35) or other conditions including injury/poisoning, digestive, circulatory, nervous and respiratory disease (38).…”
Section: Intentional Self-harmmentioning
confidence: 99%
“…Eight prospective or retrospective cohort studies showed a higher rate of suicide during follow-up among people with a sickness absence spell during the study inception period, compared to those without sickness absence [33][34][35][36][37][38][39][40]. Multiple of these studies observed that people with longer sickness absence spells, and those with multiple spells, are at increased risk of suicide than those with short or no absences [33,34,37,39], and that those whose absence is due to mental health conditions are at increased risk of suicide [35][36][37][38][39].…”
Section: Plos Global Public Healthmentioning
confidence: 99%
“…Compared with those countries with lower economies, countries with stronger economic power have stronger public health service capabilities, correspondingly stronger detection capabilities, and more resources and capabilities to detect infected patients. This has a direct and positive effect on the number of diagnoses [ 46 ].…”
Section: Analysis Of Covid-19 Epidemic and Public Health Service Cmentioning
confidence: 99%